Ethical and Methodological Challenges of Implementing Social Work Survey Research in Schools: A Perspective from the Suburban United States - Chrisann Newransky; Stavroula Kyriakakis; Karishma D. Samaroo; Delores D. Owens; Azahah Abu Hassan Shaari (International Journal of School Social Work, 2020)
Many researchers view schools as the ideal setting to study social and behavioral interventions with youth. As trusted community-based organizations, schools are natural partners for social work researchers who focus on bridging the needs of the most vulnerable populations. Awareness and consideration of critical issues related to conducting research within the school system enables social work researchers to plan and conduct rigorous studies while developing sustainable partnerships with schools. This article outlines key ethical and methodological challenges of conducting school-based survey research, and shares lessons learned and recommendations from the evaluation of a dating violence prevention curriculum implemented in U.S. suburban high schools.
Keywords: school-based research; survey research; evaluation; research ethics; parental consent; incentives; school partnerships